DISCLOSURE AND ASYMMETRY INFORMATION EFFECT ON THE COST OF EQUITY CAPITAL WITH AUDIT COMMITTEE AS A MODERATING VARIABLE - Murtanto; Nata, Sofian; Noor, Ice Nasyrah; Oktaviani, Ayu Aulia (LEMBAGA PENERBIT FAKULTAS EKONOMI DAN BISNIS UNIVERSITAS TRISAKTI, 2024)
In this study, we will use the audit committee as a moderator to look at how various disclosures such as general information, mandated disclosure, and corporate social responsibility affect the cost of equity capital. Specifically, this study relies on secondary data mined from sustainability and annual reports. This study's population consists of energy, consumer non-cyclical, and consumer cyclical enterprises that have been listed on the Indonesia Stock Exchange (BEI) between 2019 and 2022. This study uses the technique of purposive sampling to gather data. There is an imbalance in the data set since various companies had varied numbers of observations during the study period. From 2019 through 2022, 133 companies' data sets were deemed suitable for inclusion in the sample. This data study makes use of Eviews, a quantitative data analysis tool, to analyze the data using panel data analysis. Findings suggest that disclosures pertaining to general information and obligatory disclosures reduce the cost of equity capital, however disclosures on information asymmetry and corporate social responsibility do not. Audit committees have limited power to affect equity capital costs by reducing the impact of information asymmetry and increasing CSR disclosure; however, they are unable to do so with forced disclosure or general information disclosure